O neustreznosti enačenja obleke z nošo - Knific, Bojan (Etnolog. Nova vrsta (Ljubljana), 2009)
The article deals with the terms used from the 16th century on to describe dressing and what resulted from it - dresses. It dedicates special attention to how (in)adequate the term noša (costume in the sense of ethnic dress) is for denoting what people wear on their bodies, and in comparison prefers the terms dress and dressing style. Dress is a term used in science as well as in everyday speech, but unlike noša the range of meanings it covers is not limited temporally, socially, or spatially, and the same is true of dressing style, a term which because of its almost exclusively scientific use has not acquired any additional meanings distorting its original definition in the part three decades.
Keywords: Knific, Bojan, 1971-; ethnology; etnologija; oblačilna kultura; noša; terminologija; terminology; Slovenci; Slovenes; zgodovinski pregledi